Accounting Practices, Financial Literacy And Financial Performance Of Micro, Small And Medium Enterprises - Onyango Thadeus, Owino; Simiyu, Gabriel; Ombaba, Mwengei (Profesional Muda Cendekia Publishing, 2023)
This study examines how financial literacy moderates the link between accounting practices and financial performance of MSMEs in the Republic of Kenya. Micro, Small and Medium Enterprises (MSMEs) are significant in developing many economies by creating employment, alleviating poverty and food insecurity, and contributing to the Gross Domestic Product. Despite their significance, MSMEs face multiple challenges that affect their capacity to achieve desired economic outcomes. The study employed an explanatory research design and utilized simple random sampling to select a representative sample. Data was collected from 398 managers/owners of MSMEs using a self-administered questionnaire. The hierarchical regression model was used to test the study hypothesis in SPSS vs.23. The study revealed that accounting practices and financial literacy have a positive and significant influence on MSMEs' financial performance. In addition, results show that financial literacy moderates the relationship between accounting practices and financial performance. The study underlines the importance of accounting approaches and financial literacy in improving MSMEs’ financial performance in developed and emerging nations. Given the scarcity of research in this context, it is critical to employ financial literacy as a moderating variable. The interaction results contribute to the body of knowledge and serve as a catalyst for improving the association between accounting practices and financial performance.